A Rare Case of Late Onset Familial Long QT Syndrome Presented with Recurrent Cardiac Arrest, Complete Heart Block, and NSTEMI - Hendra Gunawan; Muhammad Yamin (Acta Medica Indonesiana, 2025)
Long QT Syndrome (LQTS) is a rare cardiac condition whose etiology is acquired or congenital. It has a wide range of clinical manifestations ranging from asymptomatic to sudden cardiac death due to malignant arrhythmia such as ventricular tachycardia. Congenital LQTS usually occurs at an early age in the form of prolonged QT interval in ECG examination, but such a condition may occur in later life. Therefore, QT interval should be assessed thoroughly to minimize the risk of iatrogenic ventricular tachycardia. A 72-year-old Javanese female with recurrent syncope episodes for 8 months was referred to the emergency department for temporary pacemaker implantation due to a complete heart block and NSTEMI. Family history revealed a first-degree family history of sudden cardiac death. She had a history of recurrent cardiac arrest due to ventricular arrhythmia and was treated with amiodarone continuous intravenous infusion in the previous hospital. During examination in the emergency department, she experienced another episode of cardiac arrest due to ventricular arrhythmia. Electrocardiogram examination pre-cardiac arrest revealed a complete heart block, atrial rate 60 bpm, ventricle rate 60 bpm, T Inversion in I, aVL, V2-V6, with prolonged QT interval (QT 616 ms, QTc 578 ms). Thus, amiodarone was subsequently stopped, and defibrillation was administered under ACLS guidelines. After the return of spontaneous circulation, revascularization was conducted due to ongoing typical chest pain and increased troponin level (117 ng/mL) to the LAD. Despite optimal revascularization and normal electrolyte level (Sodium 137 mEq/L, Potassium 3.8 mEq/L, Chloride 104.5 mEq/L), prolonged QT interval was observed in the patient until the 9th day post-revascularization and the double-chamber pacemaker implantation was conducted on patient. Thus, the prolonged QT interval subsided after double-chamber pacemaker implantation. Long QT Syndrome may occur at any period of life and may be asymptomatic. A thorough ECG examination before commencing treatment on a patient was pivotal to preventing malignant arrhythmia.